PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK PROBLEM SOLVING TERHADAP PENYESUAIAN DIRI SISWA KELAS X - Aprilianti, Chintya; Eti Rohaeti, Euis; Rismawati Siddik, Riesa (IKIP Siliwangi, 2025)
Based on real-world phenomena, this article found that some students still struggle with low self-adjustment, which can be caused by internal and external factors. When someone has low self-adjustment, they worry that they will not be able to adapt to their new environment. Finding out how well students adapt to using the services offered is the main objective of this study. This study used an explanatory sequential design and a mixed-method approach, both of which were created by Creswell. Thirteen students from grade X at SMA Pasundan 1 Cimahi became the subjects in this study; they were evenly divided between the experimental and control groups. Interviews, observations, and personal adjustment surveys were some of the methods used to collect data. According to the findings of this study, there has been a significant change in comparing the scores on the pretest and posttest. The findings of this study revealed that the experimental group obtained an average n-gain score of 63.7%, which placed them in the highly effective category, compared to the control group's average score of 31.2%, which placed them in the ineffective category. The results of the study indicate that group guidance using problem-solving strategies for students' self-adjustment is effective, based on interviews and observations. At the initial meeting, some children were still too shy to speak up and give suggestions for the group project, which was both a reaction and a hindrance.